Averting Burnout in Academia; Parenting as Lightning Rod - Heijstra, Thamar Melanie, 1981- (2014)
The academic profession is characterised by autonomy and flexibility but also by a competitive work atmosphere and high workload, which makes it a perfect breeding ground for burnout. Foreign studies have shown burnout rates among academics up to 20 per cent. As for its permeable boundaries, academics have called working in academia a lifestyle rather than a profession. In Iceland it is uncommon to delay or forgo family formation because of career making, even though discourses on work-family conflict identify this combination as stressful at times. This study revolves around the manner in which parenting can influence the work-related well-being of male and female academics as measured by burnout. Data derive from 20 face-to-face interviews with academics, and an online survey that was send to all academics in Iceland, containing an adjusted version of the Maslach Burnout Inventory. Independent sample t-tests and ANOVA analyses show that raising children can up to some extent enhance feelings of emotional exhaustion and depersonalisation but that it can also add to feelings of personal achievement which in turn work against burnout. Parenting therefore functions as lighting rod, assisting academics to structure their daily lives and forcing them to spend time away from work.